Penerapan metode berpasangan dalam meningkatkan kemampuan passing bawah pada permainan bola volli mini - Aryanto, Hermawan Noval; Nur, Suaib; Hidayat, Rachmat (Universitas Hamzanwadi, 2023)
This research aims to determine the improvement of underhand passing skills by implementing the partnered approach method in mini volleyball. The study employs a one-group pretest and posttest design, conducted solely on a single group without a control or comparative group. The sample consists of 30 students participating in extracurricular volleyball activities. The sampling technique used in this study is total sampling. The results of this research indicate that the partnered training method proves to be effective in enhancing the learning outcomes of Mini Volleyball's underhand passing technique among students of SMA Negeri 5 Palopo. This is evident through the increase in the average scores of students following a series of training and interventions. The significant improvement is observed in the comparison of the average scores between the pretest and post-test phases. In the pretest phase, the average score of students was 67, whereas in the post-test phase, the average score increased to 80. Furthermore, based on the findings and t-test analysis, the obtained P-value or Sig. (2-tailed) is smaller than α (0.000 < 0.05). This indicates the acceptance of the alternative hypothesis (H1) and the rejection of the null hypothesis (H0).